Depiction of Machismo through Castillo Brothers in Oscar Hijuelos’ The Mambo Kings Play Songs of Love - Supiastutik Supiastutik; Septania Alya Rakhman; Syamsul Anam (Journal of Feminism and Gender Studies, 2024)
The Mambo Kings Play Songs of Love (1989) is a novel by Oscar Hijuelos, a Cuban-American writer. It talks about the lives of Cesar and Nestor Castillo, Cuban immigrants who live in America to pursue their dreams as musicians. The novel strongly connects to Latin American culture. The Castillo brothers are known for embracing their "Cubanness" as men. Men in Spanish-speaking countries are recognized for their masculine solid pride. Their strong masculine pride is often associated with an exaggeration of their masculinity. People often call it machismo. Machismo, derived from destructive aspects such as aggressiveness, womanizing, emotional withdrawal, and male chauvinism, is known for having harmful outcomes for men who embed it. Operating Hall's Theory of Representation and Kupers' concept of toxic masculinity, this research aims to show how the Castillo brothers represent machismo and reveal the ideology of Oscar Hijuelos' regarding machismo. This research is conducted as qualitative research, utilizing narratives and dialogues. The study found that Cesar's practice of machismo through the act of being a Latin lover affects his participation in alcoholism and resistance to professional help. Besides, Nestor's practice of machismo for being a "man with muscle" eventually leads him to depression, anxiety, and rejection of therapy. It is acknowledged their status as immigrants heighten their practices of machismo. Through his writing, the author expects to criticize machismo.